Electricity Demand and Supply Planning Analysis for Sumatera Interconnection System using Integrated Resources Planning Approach - Suhono Suhono; Sarjiya Sarjiya; Sasongko Pramono Hadi (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2019)
The Sumatra interconnection system, which is the second-largest electricity system in Indonesia, is often experiencing rolling blackouts. That caused by a lack of supply from the power generating system of Sumatra. The Government has planned to develop new power plants through the fast track program (FTP). Until 2015, either power outages and supply shortages are still common. Therefore, an analysis of long-term electricity planning needed to support energy security in Sumatra. The Sumatra electricity system was modelled using integrated resource planning as a framework and the long-range energy alternative planning (LEAP) software as a tool to build and simulate the model. Three groups of scenarios will be compared are the fast track program (FTP) scenario, the biofuel mandatory (BM) scenario and optimization (OPT) scenario. The results show that the implementation of DSM programs through energy conservation scenario would be able to reduce the electricity demand in the future. On the other side, the alternative scenario shows that the electricity deficit could be resolved in 2022, while the optimization scenario shows that energy diversity would resolve the electricity crisis in the Sumatra interconnection system.